Women from Traditional Islamic Educational Institutions in Indonesia : Negotiating Public Spaces. - Srimulyani, Eka (IIAS publications series. Monographs, 2012)
Until currently there have been no specific publications, particularly in English, on women in traditional Islamic educational institutions in Indonesia, known as pesantren, which played a significant role in shaping the gender issues in the Indonesian Muslim community. This informative and insightful book contributes to two booming fields in Indonesian studies: the study of Islam and the study of Muslim women. It also adds a new perspective to the English-language literature on Muslim women outside the Middle-Eastern or Sub-Indian continent communities context, which used to dominate the scholarly discussion or publication in this field.